Variability of mitochondrial DNA D-loop sequences in Zabaikalskaya horse breed - L. A. Khrabrova; N. V. Blohina; B. Z. Bazaron; T. N. Khamiruev (Вавиловский журнал генетики и селекции)
The Zabaikalskaya horse is an indigenous breed of horses from Siberia with diverse use. It is characterized by e durance and good adaptability to year-round herd maintenance in the harsh conditions of the Baikal steppes. To determine the genetic characteristics of the maternal lineage of the Zabaikalskaya horse breed based on mitochondrial DNA polymorphisms, we collected hair samples from 31 horses belonging to breeding farms in the Trans-Baikal Territory. Analysis of the 530 bp sequence of the mtDNA D-loop was performed using the maximum composite likelihood (MCL) model in combination with bootstrap analysis. When studying the polymorphism of the hypervariable region of the mtDNA D-loop in Zabaikalskaya horses, we identified 31 haplotypes representing 8 haplogroups: B, C, G, H, L, M, Q and R according to modern classification. The sequenced fragment of the D-loop from nucleotide position 15471 to 16000 contained 17 polymorphic sites, mainly represented by the A→G, G→A and T→C transitions. The haplogroups Q (25.81 %), B (19.35 %), G (16.13 %) and H (12.90 %) were prevailing in the mtDNA structure of this breed. Genetic analysis of the mitochondrial genome of the Zabaikalskaya horse revealed a high level of diversity of haplotypes and haplogroups, which are typical for the horse populations of Eurasia.